Is dexmedetomidine superior to non-dexmedetomidine sedatives (particularly propofol) for sedation in critically ill patients with septic shock? A systematic review and meta-analysis of randomized controlled trials - Gao, Xinjing; Li, Zhaoting; Li, Zhibo; Qin, Yingzhi; Ren, Jie; Zhang, Kai; Wang, Wenjiao (Frontiers in Medicine, 2025)
BackgroundDexmedetomidine (DEX) and propofol (PROP) are both recommended as first-line short-acting sedative-analgesic agents for sepsis patients. However, existing studies have reported inconsistent clinical outcomes potentially attributable to their distinct hemodynamic profiles. The aim of our study was to systematically evaluate the comparative clinical efficacy and safety of DEX vs. non-Dexmedetomidine sedatives (particularly Propofol) in patients with septic shock.MethodsThe study protocol was prospectively registered on PROSPERO (CRD42024626139). Randomized controlled trials (RCTs) meeting eligibility criteria were systematically searched up to December 2024. Statistical analyses were performed using RevMan 5.4, and trial sequential analysis (TSA) was employed to determine the required sample size.Results17 RCTs were enrolled with 1,422 patients. Compared with non-DEX group, DEX group presented significantly reduced 28-day mortality (odds ratio [OR] 0.68, 95% CI 0.49–0.94, p = 0.02), lower IL-6 (mean difference [MD] −3.11 ng/L, 95% CI −5.32 to −0.90, p = 0.006) and TNF-α (MD −0.21 ng/L, 95% CI −0.30 to −0.12, p < 0.001). Importantly, the incidence of adverse effects did not increase compared to non-DEX groups, as evidenced by delirium (OR 0.82, 95% CI 0.34 to 1.97, p = 0.66), bradycardia (OR 1.36, 95% CI 0.66 to 2.78, p = 0.40), and hypotension (OR 1.38, 95% CI 0.59 to 3.19, p = 0.46). In the subgroup analysis, PROP showed no significant differences over DEX for key clinical outcomes, including: 28-day mortality and duration of invasive mechanical ventilation (IMV), length of stay in Intensive Care Unit (ICU LOS), etc. Regrettably, existing RCTs lacked sufficient data regarding inflammatory biomarkers and adverse event profiles above in direct comparisons between DEX and PROP. TSA on 28-day mortality between DEX and PROP indicated that a minimum of 1,269 additional participants would have required to achieve conclusive evidence (α = 0.10; β = 0.30; relative risk reduction [RRR] = 12.5%).ConclusionDEX demonstrated superiority over non-DEX sedatives in critically ill patients with septic shock without increasing hemodynamic adverse events. However, current evidence showed no significant differences between DEX and PROP, warranting further high-quality RCTs for definitive conclusions.